2018
DOI: 10.17977/um032v0i0p125-134
|View full text |Cite
|
Sign up to set email alerts
|

Pendampingan Pemetaan Potensi Pertanian Lokal Dan Pengelolaannya Dalam Mendukung Agro Ekowisata Kecamatan Kandangan Kabupaten Kediri

Abstract: Pengabdian mayarakat ini bertujuan untuk (1) Meningkatkan kesadaran masyarakat dalam mengenali potensi pertanian lokal yang bernilai ekonomis. (2) Meningkatkan kemampuan masyarakat desa, dalam mengolah potensi pertanian lokal sebagai pendukung agro ekowisata. Kegiatan pengabdian masyarakat ini dilakukan melalui pendampingan kepada masyarakat, terutama pada ibu-ibu PKK. Mata pencaharian masyarakat saat yang ini di sektor pertanian. Dari hasil pengabdian masyarakat ini teridentifikasi potensi pertanian lokal yan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…It can be concluded that public awareness of the performance indicators of post-tin mining in agro-ecotourism is considered appropriate. According to Sugiyono (2004) value 60-79% means agree, so we can conclude that public perception of post-mining tin indices is considered consistent .…”
Section: Community Perception Of Pre-management Of Post-tin Mining La...mentioning
confidence: 72%
“…It can be concluded that public awareness of the performance indicators of post-tin mining in agro-ecotourism is considered appropriate. According to Sugiyono (2004) value 60-79% means agree, so we can conclude that public perception of post-mining tin indices is considered consistent .…”
Section: Community Perception Of Pre-management Of Post-tin Mining La...mentioning
confidence: 72%
“…The development of the agro-eco tourism must suit to the potential of the area itself. For instance, the study of the potential development conducted in Kandangan Region, in Kediri district, found that this region possesses some potentialas in their agricultural comodity which are invaluable to the region, such as the the durians, cloves, coffee, snake fruits, mangosteens, bananas, oyster mushrooms, and dairy cows, which could sustain the development of the agro-eco tourism in the region (Sumarmi, et al, 2018). Other potentials of the agro-eco tourism are the tourism spots, the uniqueness of the farming culture, the facilities, public support, the development of the human resources, community and associations, the agro-tourism program, associations which sopport/organize the agro-tourism, services or the agro-tourism, government support and related organizations, also a potential colloboration with relatable parties in the business (Budiarti, et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Wisatawan yang berkunjung dapat melakukan kegiatan fisik seperti menyusuri jalan setapak atau kegiatan jogging. Selain itu, terdapat rute yang bisa dilalui melalui jalan kaki atau menggunakan sepeda motor menuju Coban Sumber Jodo (Sumarmi et al, 2018). Masyarakat dapat memanfaatkan peluang ini untuk membangun fasilitas yang menunjang aktivitas wisatawan.…”
Section: Keunikan Wilayahunclassified
“…Berdasarkan pengabdian yang pernah dilakukan, mayoritas masyarakat di Desa Medowo memiliki mata pencaharian di sektor pertanian. Pengabdian ini berhasil mengubah mainset dan skill masyarakat untuk mengolah hasil bumi yang bernilai jual tinggi (Sumarmi et al, 2018). Akan tetapi, hal ini masih belum mampu meningkatkan ekonomi masyarakat Desa Medowo karena dibandingkan produk khas Kabupaten Kediri lainnya, produk hasil produksi masyarakat Desa Medowo masih kalah popularitasnya.…”
unclassified